Process for enriching copper and nickel from secondary nickel return material

By reducing and smelting the secondary nickel return material with cassiterite and slag-forming agent, combined with sulfuric acid solution leaching and hydrogen peroxide precipitation, the problem of difficult copper-nickel separation in the secondary nickel return material was solved, and efficient copper-nickel recovery and resource utilization were achieved.

CN120666179AActive Publication Date: 2025-09-19浙江环益资源利用股份有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510895452.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-30
Publication Date
2025-09-19
Estimated Expiration
2045-06-30

AI Technical Summary

Technical Problem

The existing technology has problems such as high energy consumption, serious environmental pollution and low metal recovery rate when processing secondary nickel return materials. In particular, it is difficult to separate copper and nickel in copper smelting slag, resulting in waste of resources.

Method used

Secondary nickel return material, cassiterite and slag-forming agent are mixed and smelted in a reducing atmosphere to form alloy material and slag phase. Cassiterite is reduced to Sn to lower the melting point. Calcium oxide, magnesium carbonate, quartz sand and starch slag-forming agent are combined to promote separation. Copper and nickel enrichment is achieved through sulfuric acid solution leaching and hydrogen peroxide precipitation.

Benefits of technology

The recovery rate of copper and nickel is improved, the smelting temperature and energy consumption are reduced, the dust loss is reduced, and efficient copper and nickel separation and recovery are achieved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of metallurgy, and particularly discloses a process for enriching copper and nickel from secondary nickel return charge, the secondary nickel return charge, cassiterite and a slag former are blended and then calcined in a reducing atmosphere, the main component of the cassiterite is SnO2, the cassiterite is reduced into Sn in the reducing atmosphere, the Sn has a lower melting point, the melting point of the Sn is higher than that of the slag former, and the copper and nickel are enriched in the secondary nickel return charge. The tin-nickel-copper low-melting-point alloy has the advantages that the tin-nickel-copper low-melting-point alloy can permeate into alloy crystal grains of the secondary nickel return material, the original compact structure is destroyed, the dissolving and leaching difficulty of nickel and copper in the secondary nickel return material is effectively reduced, and then the dissolving and leaching efficiency is improved; and meanwhile, the cassiterite is doped, so that the smelting temperature is reduced, and compared with the smelting temperature of about 1400-1500 DEG C in the prior art, the smelting can be performed at 1000-1100 DEG C, so that the energy consumption is saved, and the tin in the cassiterite can be effectively recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallurgy, and in particular to a process for enriching copper and nickel by using secondary nickel return material. Background Art

[0002] Secondary nickel returns generally refer to recyclable materials such as nickel-containing scrap and scrap generated during nickel smelting and processing. After proper treatment, these materials can be put back into production, representing an important form of nickel resource recycling. As a key source of secondary nickel returns, the treatment and recycling of copper smelting slag is of great significance.

[0003] Nickel pyrometallurgy primarily uses nickel-containing ores, such as nickel sulfide, as raw materials. Since copper and nickel are commonly found in naturally occurring ores, flotation is required to separate these polymetallic ores. This separation yields nickel concentrate with a higher nickel content and copper concentrate with a higher copper content. These concentrates are then sent to nickel and copper pyrometallurgy systems for smelting, respectively.

[0004] During this process, a small amount of nickel remains in the separated copper concentrate. This nickel is discharged as slag during the copper smelting process, forming copper smelting slag. This slag mainly includes Kaldo slag and autothermal furnace slag, typically containing between 35-40% copper and 14-16% nickel, with small amounts of elements such as iron and cobalt. Due to its high copper content, it cannot be directly sent to the nickel pyrometallurgical system for processing; at the same time, it contains a large amount of nickel, and if sent to the copper pyrometallurgical system for processing, it will cause serious nickel loss. This results in a large amount of slag being stored in a backlog, resulting in a huge waste of resources. Currently, the methods for processing this type of secondary nickel return mainly include pyrometallurgical and hydrometallurgical methods.

[0005] Although the current pyrometallurgical smelting process is relatively mature, it still has problems such as high energy consumption, serious environmental pollution, and low metal recovery rate. Therefore, there is an urgent need to improve the existing process to increase the metal recovery rate. Summary of the Invention

[0006] In view of the shortcomings of the prior art, the object of the present invention is to provide a process for enriching copper and nickel by secondary nickel return.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A process for enriching copper and nickel from secondary nickel return material, comprising the following steps:

[0009] S1. Preparation of alloy material and slag phase

[0010] The secondary nickel return material, cassiterite and slag forming agent are mixed evenly and smelted in a reducing atmosphere to obtain alloy material and slag phase.

[0011] In this step, the secondary nickel return material and cassiterite are firstly crushed and passed through a 40-mesh sieve, and then mixed with a slag-forming agent.

[0012] In this step, the mass ratio of the secondary nickel return material, cassiterite and slag forming agent is 50:20-30:15-25. In some embodiments of the present invention, for example, 50:20:15, 50:20:20, 50:20:25, 50:25:15, 50:25:25, 50:30:15, 50:30:20, and 50:30:25 can be selected, but it is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0013] In this step, the slag-forming agent is composed of calcium oxide, magnesium carbonate, quartz sand and starch.

[0014] In the technical solution disclosed in the present invention, the mass ratio of calcium oxide, magnesium carbonate, quartz sand and starch is 20-40:10-15:10-15:10-20.

[0015] In this step, the reducing atmosphere is a mixed atmosphere of CO and CO2, and the volume fraction of CO in the reducing atmosphere is 30-40%.

[0016] In this step, the specific process of smelting in a reducing atmosphere is: first heating to 600-700°C, keeping warm for 1-2 hours, then heating to 1000-1100°C, keeping warm for 1-2 hours.

[0017] In the present invention, secondary nickel return material, cassiterite and a slag-forming agent are blended and then calcined in a reducing atmosphere. The cassiterite has SnO2 as a main component and is reduced to Sn in the reducing atmosphere. Sn has a relatively low melting point and can penetrate between alloy grains of the secondary nickel return material, destroying the original dense structure to form a tin-nickel-copper low-melting-point alloy, thereby effectively reducing the difficulty of dissolving and leaching nickel and copper in the secondary nickel return material and thereby improving the dissolving and leaching efficiency. At the same time, the smelting temperature is reduced by adding the cassiterite. Compared with the smelting temperature of about 1400-1500° C. in the prior art, the present invention can perform smelting at 1000-1100° C., thereby saving energy consumption and effectively recycling the tin in the cassiterite.

[0018] The slag-forming agent provided by the present invention is composed of calcium oxide, magnesium carbonate, quartz sand and starch. Calcium oxide acts as an alkaline flux and reacts with acidic oxides in the material to generate a low-melting-point silicate slag phase, thereby promoting the separation of the alloy material and the slag phase and inhibiting impurities such as iron and silicon from entering the alloy phase. Magnesium carbonate decomposes into magnesium oxide and carbon dioxide at high temperatures. Magnesium oxide acts as a slag phase stabilizer and can form mineral phases such as forsterite (Mg2SiO4), thereby improving the high-temperature resistance of the slag and preventing the slag phase from being too thin or too thick. The carbon dioxide gas generated by the decomposition can form a localized slag in the smelting system. The tiny bubbles in the smelting mixture help to suspend the fine particles in the secondary nickel return material, allowing them to fully contact with the reducing atmosphere, improve the reduction efficiency, and thus be beneficial to the enrichment of copper and nickel; quartz sand reacts with calcium oxide and magnesium oxide to form a composite silicate slag phase, which makes the slag phase have good fluidity to achieve efficient separation; starch acts as a binder in the mixing stage to enhance the bonding strength between material particles and reduce dust loss. At the same time, it decomposes into carbon when heated in the early stage of smelting, acting as a supplementary reducing agent to strengthen the reduction of cassiterite (SnO2) to metallic tin and promote the formation of tin, copper and nickel alloys.

[0019] S2. Preparation of leachate

[0020] The alloy material obtained in step S1 is crushed and ground, and then added to a sulfuric acid solution, and then sodium chlorate is added, and the mixture is heated for leaching to obtain a leachate.

[0021] In this step, the alloy material is crushed and ground and then passed through a 40-mesh sieve.

[0022] In this step, the solid-liquid ratio of the alloy material and the sulfuric acid solution is 1 g:10-20 mL. In some embodiments of the present invention, for example, 1 g:10 mL, 1 g:12 mL, 1 g:14 mL, 1 g:15 mL, 1 g:16 mL, 1 g:17 mL, 1 g:18 mL, 1 g:19 mL, and 1 g:20 mL can be selected, but the ratio is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0023] Specifically, the concentration of the sulfuric acid solution is 5-10 mol / L, for example, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L can be selected, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0024] In this step, the mass ratio of the alloy material to sodium chlorate is 1:2-2.5, for example, 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5 can be selected, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0025] In this step, the heating and leaching temperature is 70-80°C, for example, 70°C, 72°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, and 80°C can be selected; the heating and leaching time is 6-8h, for example, 6h, 6.5h, 7h, 7.5h, and 8h can be selected, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] S3, prepare the filtrate enriched with copper and nickel

[0027] The pH of the leaching solution is adjusted to 2-3, hydrogen peroxide is added, and the solution is filtered to obtain a filtrate enriched with copper and nickel.

[0028] In this step, Fe 2+ Oxidized to Fe 3+ , Fe 3+ and Sn 4+ The precipitation is carried out under the condition of pH 2-3, and the precipitation is separated by filtration, and copper and nickel are enriched in the filtrate.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The present invention blends secondary nickel return material, cassiterite and a slag-forming agent, and then calcines them in a reducing atmosphere. The main component of the cassiterite is SnO2, which is reduced to Sn in the reducing atmosphere. Sn has a low melting point and can penetrate into the alloy grains of the secondary nickel return material, destroying the original dense structure to form a tin-nickel-copper low-melting-point alloy, effectively reducing the difficulty of dissolving and leaching nickel and copper in the secondary nickel return material, thereby improving the dissolving and leaching efficiency; at the same time, by adding cassiterite, the smelting temperature is reduced. Compared with the smelting temperature of about 1400-1500°C in the prior art, the present invention can carry out smelting at 1000-1100°C, saving energy consumption while effectively recycling the tin in the cassiterite.

[0031] (2) The slag-forming agent provided by the present invention is composed of calcium oxide, magnesium carbonate, quartz sand and starch. Calcium oxide acts as an alkaline flux and reacts with the acidic oxides in the material to form a low-melting-point silicate slag phase, which promotes the separation of the alloy material and the slag phase and inhibits impurities such as iron and silicon from entering the alloy phase. Magnesium carbonate decomposes into magnesium oxide and carbon dioxide at high temperatures. Magnesium oxide acts as a slag phase stabilizer and can form mineral phases such as forsterite (Mg2SiO4), thereby improving the high-temperature resistance of the slag and preventing the slag phase from being too thin or too thick. The carbon dioxide gas generated by the decomposition can form a localized The tiny bubbles in the slag help to suspend the fine particles in the secondary nickel return material, so that they can fully contact with the reducing atmosphere, improve the reduction efficiency, and thus be beneficial to the enrichment of copper and nickel; quartz sand reacts with calcium oxide and magnesium oxide to form a composite silicate slag phase, which makes the slag phase have good fluidity to achieve efficient separation; starch acts as a binder in the mixing stage to enhance the bonding strength between material particles and reduce dust loss. At the same time, it decomposes into carbon when heated in the early stage of smelting, which acts as a supplementary reducing agent to strengthen the reduction of cassiterite (SnO2) to metallic tin and promote the formation of alloys between tin and copper and nickel. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.

[0033] It should be noted that, unless otherwise specified, all chemical reagents involved in the present invention were purchased through commercial channels.

[0034] The secondary nickel return material used in the embodiment of the present invention is copper-nickel-containing copper smelting slag, whose main components are: Ni 16.37%, Cu 38.23%, Fe 4.47%, Co 0.16%;

[0035] The SnO2 content in cassiterite is 98.5% and the Fe content is 0.62%;

[0036] The mesh size of calcium oxide and magnesium carbonate is 80 mesh;

[0037] The mesh size of quartz sand is 200 mesh;

[0038] The starch is corn starch.

[0039] Example 1

[0040] A process for enriching copper and nickel from secondary nickel return material, comprising the following steps:

[0041] S1. The secondary nickel return material and cassiterite were crushed and passed through a 40-mesh sieve respectively, and then 50 parts of the secondary nickel return material, 25 parts of the cassiterite and 20 parts of the slag-making agent were mixed evenly, wherein the slag-making agent was composed of calcium oxide, magnesium carbonate, quartz sand and starch, and the mass ratio of calcium oxide, magnesium carbonate, quartz sand and starch was 30:15:15:15. In a reducing atmosphere, the temperature was first increased to 600°C at a heating rate of 50°C / min, and kept warm for 2h, and then increased to 1000°C at a heating rate of 20°C / min, and kept warm for 1h, wherein the reducing atmosphere was a mixed atmosphere of CO and CO2, the volume fraction of CO in the reducing atmosphere was 30%, and the flow rate of the reducing atmosphere was 10m 3 / h, to obtain alloy material and slag phase;

[0042] S2. The alloy material obtained in step S1 was crushed and ground, and then passed through a 40-mesh sieve. The alloy material was added to an 8 mol / L sulfuric acid solution at a solid-to-liquid ratio of 1:15, and then sodium chlorate was added. The mass ratio of the alloy material to sodium chlorate was 1:2, and the mixture was heated at 70° C. for 8 h to obtain a leachate.

[0043] S3. The pH of the leachate is adjusted to 2 with a 1 mol / L Na2CO3 solution, and hydrogen peroxide is added. The volume ratio of the leachate to the hydrogen peroxide is 1:2, and the mass fraction of the hydrogen peroxide is 40%. Tin and iron elements are precipitated from the leachate, and the solution is filtered to obtain a filtrate enriched with copper and nickel.

[0044] The nickel and copper contents in the filtrate of step S3 were determined by ICP-OES: nickel recovery (%) = mass of nickel in filtrate / mass of nickel in secondary nickel return × 100%, copper recovery (%) = mass of copper in filtrate / mass of copper in secondary nickel return × 100%. The nickel recovery was 96.6%, and the copper recovery was 97.2%.

[0045] Example 2

[0046] A process for enriching copper and nickel from secondary nickel return material, comprising the following steps:

[0047] S1. The secondary nickel return material and cassiterite were crushed and passed through a 40-mesh sieve respectively. Then, 50 parts of the secondary nickel return material, 20 parts of the cassiterite and 15 parts of the slag-making agent were mixed evenly, wherein the slag-making agent was composed of calcium oxide, magnesium carbonate, quartz sand and starch, and the mass ratio of calcium oxide, magnesium carbonate, quartz sand and starch was 20:10:15:20. In a reducing atmosphere, the temperature was first increased to 600°C at a heating rate of 50°C / min and kept warm for 2h, and then increased to 1000°C at a heating rate of 20°C / min and kept warm for 1h. The reducing atmosphere was a mixed atmosphere of CO and CO2, the volume fraction of CO in the reducing atmosphere was 30%, and the flow rate of the reducing atmosphere was 10m 3 / h, to obtain alloy material and slag phase;

[0048] S2. The alloy material obtained in step S1 was crushed and ground, and then passed through a 40-mesh sieve. The alloy material was added to an 8 mol / L sulfuric acid solution at a solid-to-liquid ratio of 1:15, and then sodium chlorate was added. The mass ratio of the alloy material to sodium chlorate was 1:2, and the mixture was heated at 70° C. for 8 h to obtain a leachate.

[0049] S3. The pH of the leachate is adjusted to 2 with a 1 mol / L Na2CO3 solution, and hydrogen peroxide is added. The volume ratio of the leachate to the hydrogen peroxide is 1:2, and the mass fraction of the hydrogen peroxide is 40%. Tin and iron elements are precipitated from the leachate, and the solution is filtered to obtain a filtrate enriched with copper and nickel.

[0050] The nickel and copper contents in the filtrate of step S3 were determined according to the method of Example 1, and the nickel and copper recovery rates were calculated. The nickel recovery rate was 95.8%, and the copper recovery rate was 96.9%.

[0051] Example 3

[0052] A process for enriching copper and nickel from secondary nickel return material, comprising the following steps:

[0053] S1. The secondary nickel return material and cassiterite were crushed and passed through a 40-mesh sieve respectively, and then 50 parts of the secondary nickel return material, 30 parts of the cassiterite and 25 parts of the slag-making agent were mixed evenly, wherein the slag-making agent was composed of calcium oxide, magnesium carbonate, quartz sand and starch, and the mass ratio of calcium oxide, magnesium carbonate, quartz sand and starch was 20:15:15:20. In a reducing atmosphere, the temperature was first increased to 600°C at a heating rate of 50°C / min, and kept warm for 2h, and then increased to 1000°C at a heating rate of 20°C / min, and kept warm for 1h, wherein the reducing atmosphere was a mixed atmosphere of CO and CO2, the volume fraction of CO in the reducing atmosphere was 30%, and the flow rate of the reducing atmosphere was 10m 3 / h, to obtain alloy material and slag phase;

[0054] S2. The alloy material obtained in step S1 was crushed and ground, and then passed through a 40-mesh sieve. The alloy material was added to an 8 mol / L sulfuric acid solution at a solid-to-liquid ratio of 1:15, and then sodium chlorate was added. The mass ratio of the alloy material to sodium chlorate was 1:2, and the mixture was heated at 70° C. for 8 h to obtain a leachate.

[0055] S3. The pH of the leachate is adjusted to 2 with a 1 mol / L Na2CO3 solution, and hydrogen peroxide is added. The volume ratio of the leachate to the hydrogen peroxide is 1:2, and the mass fraction of the hydrogen peroxide is 40%. Tin and iron elements are precipitated from the leachate, and the solution is filtered to obtain a filtrate enriched with copper and nickel.

[0056] The nickel and copper contents in the filtrate of step S3 were determined according to the method of Example 1, and the nickel and copper recovery rates were calculated; the nickel recovery rate was 97.1%, and the copper recovery rate was 97.8%.

[0057] Comparative Example 1

[0058] A process for enriching copper and nickel from secondary nickel return material, comprising the following steps:

[0059] S1. The secondary nickel return material is crushed and passed through a 40-mesh sieve. Then, 50 parts of the secondary nickel return material and 20 parts of a slag-forming agent are mixed evenly, wherein the slag-forming agent is composed of calcium oxide, magnesium carbonate, quartz sand and starch, and the mass ratio of calcium oxide, magnesium carbonate, quartz sand and starch is 30:15:15:15. In a reducing atmosphere, the temperature is first increased to 600°C at a heating rate of 50°C / min, and kept warm for 2 hours. Then, the temperature is increased to 1000°C at a heating rate of 20°C / min, and kept warm for 1 hour. The reducing atmosphere is a mixed atmosphere of CO and CO2, the volume fraction of CO in the reducing atmosphere is 30%, and the flow rate of the reducing atmosphere is 10m 3 / h, to obtain alloy material and slag phase;

[0060] S2. The alloy material obtained in step S1 was crushed and ground, and then passed through a 40-mesh sieve. The alloy material was added to an 8 mol / L sulfuric acid solution at a solid-to-liquid ratio of 1:15, and then sodium chlorate was added. The mass ratio of the alloy material to sodium chlorate was 1:2, and the mixture was heated at 70° C. for 8 h to obtain a leachate.

[0061] S3. The pH of the leachate is adjusted to 2 with a 1 mol / L Na2CO3 solution, and hydrogen peroxide is added. The volume ratio of the leachate to the hydrogen peroxide is 1:2, and the mass fraction of the hydrogen peroxide is 40%. Tin and iron elements are precipitated from the leachate, and the solution is filtered to obtain a filtrate enriched with copper and nickel.

[0062] Comparative Example 1 Compared with Example 1, no cassiterite was added. The nickel and copper contents in the filtrate of step S3 were determined according to the method of Example 1, and the nickel and copper recovery rates were calculated. The nickel recovery rate was 65.1%, and the copper recovery rate was 72.3%.

[0063] Comparative Example 2

[0064] A process for enriching copper and nickel from secondary nickel return material, comprising the following steps:

[0065] S1. The secondary nickel return material and cassiterite were crushed and passed through a 40-mesh sieve respectively. Then, 50 parts of the secondary nickel return material, 25 parts of the cassiterite and 20 parts of the slag-making agent were mixed evenly, wherein the slag-making agent was composed of calcium oxide, quartz sand and starch, and the mass ratio of calcium oxide, quartz sand and starch was 30:15:15. In a reducing atmosphere, the temperature was first increased to 600°C at a heating rate of 50°C / min and kept warm for 2h, and then increased to 1000°C at a heating rate of 20°C / min and kept warm for 1h. The reducing atmosphere was a mixed atmosphere of CO and CO2, the volume fraction of CO in the reducing atmosphere was 30%, and the flow rate of the reducing atmosphere was 10m 3 / h, to obtain alloy material and slag phase;

[0066] S2. The alloy material obtained in step S1 was crushed and ground, and then passed through a 40-mesh sieve. The alloy material was added to an 8 mol / L sulfuric acid solution at a solid-to-liquid ratio of 1:15, and then sodium chlorate was added. The mass ratio of the alloy material to sodium chlorate was 1:2, and the mixture was heated at 70° C. for 8 h to obtain a leachate.

[0067] S3. The pH of the leachate is adjusted to 2 with a 1 mol / L Na2CO3 solution, and hydrogen peroxide is added. The volume ratio of the leachate to the hydrogen peroxide is 1:2, and the mass fraction of the hydrogen peroxide is 40%. Tin and iron elements are precipitated from the leachate, and the solution is filtered to obtain a filtrate enriched with copper and nickel.

[0068] Comparative Example 2 Compared with Example 1, no magnesium carbonate was added to the slagging agent. The nickel and copper contents in the filtrate of step S3 were determined according to the method of Example 1, and the nickel and copper recovery rates were calculated; the nickel recovery rate was 82.4%, and the copper recovery rate was 90.5%.

[0069] Comparative Example 3

[0070] A process for enriching copper and nickel from secondary nickel return material, comprising the following steps:

[0071] S1. The secondary nickel return material and cassiterite were crushed and passed through a 40-mesh sieve respectively. Then, 50 parts of the secondary nickel return material, 25 parts of the cassiterite and 20 parts of the slag-making agent were mixed evenly, wherein the slag-making agent was composed of calcium oxide, magnesium carbonate and quartz sand, and the mass ratio of calcium oxide, magnesium carbonate and quartz sand was 30:15:15. In a reducing atmosphere, the temperature was first increased to 600°C at a heating rate of 50°C / min and kept warm for 2h, and then increased to 1000°C at a heating rate of 20°C / min and kept warm for 1h. The reducing atmosphere was a mixed atmosphere of CO and CO2, the volume fraction of CO in the reducing atmosphere was 30%, and the flow rate of the reducing atmosphere was 10m 3 / h, to obtain alloy material and slag phase;

[0072] S2. The alloy material obtained in step S1 was crushed and ground, and then passed through a 40-mesh sieve. The alloy material was added to an 8 mol / L sulfuric acid solution at a solid-to-liquid ratio of 1:15, and then sodium chlorate was added. The mass ratio of the alloy material to sodium chlorate was 1:2, and the mixture was heated at 70° C. for 8 h to obtain a leachate.

[0073] S3. The pH of the leachate is adjusted to 2 with a 1 mol / L Na2CO3 solution, and hydrogen peroxide is added. The volume ratio of the leachate to the hydrogen peroxide is 1:2, and the mass fraction of the hydrogen peroxide is 40%. Tin and iron elements are precipitated from the leachate, and the solution is filtered to obtain a filtrate enriched with copper and nickel.

[0074] Comparative Example 3 Compared with Example 1, no starch was added to the slagging agent. The nickel and copper contents in the filtrate of step S3 were determined according to the method of Example 1, and the nickel and copper recovery rates were calculated; the nickel recovery rate was 86.2%, and the copper recovery rate was 92.4%.

[0075] Comparative Example 4

[0076] A process for enriching copper and nickel from secondary nickel return material, comprising the following steps:

[0077] S1. The secondary nickel return material and cassiterite were crushed and passed through a 40-mesh sieve respectively, and then 50 parts of the secondary nickel return material, 10 parts of the cassiterite and 20 parts of the slag-making agent were mixed evenly, wherein the slag-making agent was composed of calcium oxide, magnesium carbonate, quartz sand and starch, and the mass ratio of calcium oxide, magnesium carbonate, quartz sand and starch was 30:15:15:15. In a reducing atmosphere, the temperature was first increased to 600°C at a heating rate of 50°C / min, and kept warm for 2h, and then increased to 1000°C at a heating rate of 20°C / min, and kept warm for 1h, wherein the reducing atmosphere was a mixed atmosphere of CO and CO2, the volume fraction of CO in the reducing atmosphere was 30%, and the flow rate of the reducing atmosphere was 10m 3 / h, to obtain alloy material and slag phase;

[0078] S2. The alloy material obtained in step S1 was crushed and ground, and then passed through a 40-mesh sieve. The alloy material was added to an 8 mol / L sulfuric acid solution at a solid-to-liquid ratio of 1:15, and then sodium chlorate was added. The mass ratio of the alloy material to sodium chlorate was 1:2, and the mixture was heated at 70° C. for 8 h to obtain a leachate.

[0079] S3. The pH of the leachate is adjusted to 2 with a 1 mol / L Na2CO3 solution, and hydrogen peroxide is added. The volume ratio of the leachate to the hydrogen peroxide is 1:2, and the mass fraction of the hydrogen peroxide is 40%. Tin and iron elements are precipitated from the leachate, and the solution is filtered to obtain a filtrate enriched with copper and nickel.

[0080] Comparative Example 4 Compared with Example 1, the amount of cassiterite was replaced with 10 parts, and the nickel and copper contents in the filtrate of step S3 were determined according to the method of Example 1, and the nickel and copper recovery rates were calculated. The nickel recovery rate was 74.5% and the copper recovery rate was 80.1%.

[0081] Finally, it should be noted that the above embodiments do not limit the present invention in any form. Those skilled in the art will appreciate that modifications and improvements can be made based on the present invention. Therefore, any modifications or improvements made without departing from the spirit of the present invention are intended to fall within the scope of protection claimed in the present invention.

Claims

1. A process for enriching copper and nickel by secondary nickel return, characterized in that: The specific steps are as follows: S1, mixing the secondary nickel return material, cassiterite and slag forming agent uniformly, and smelting them in a reducing atmosphere to obtain an alloy material and a slag phase; S2. crushing and grinding the alloy material obtained in step S1 and adding it to a sulfuric acid solution, then adding sodium chlorate, heating and leaching to obtain a leachate; S3. Adjust the pH of the leaching solution to 2-3, add hydrogen peroxide, and filter to obtain a filtrate enriched with copper and nickel.

2. The process for enriching copper and nickel by secondary nickel return according to claim 1, characterized in that: In step S1, the mass ratio of the secondary nickel return material, cassiterite and slag forming agent is 50:20-30:15-25.

3. The process for enriching copper and nickel by secondary nickel return according to claim 1, characterized in that: In step S1, the slag-forming agent is composed of calcium oxide, magnesium carbonate, quartz sand and starch, and the mass ratio of calcium oxide, magnesium carbonate, quartz sand and starch is 20-40:10-15:10-15:10-20.

4. The process for enriching copper and nickel by secondary nickel return according to claim 1, characterized in that: In step S1, the reducing atmosphere is a mixed atmosphere of CO and CO2, and the volume fraction of CO in the reducing atmosphere is 30-40%.

5. The process for enriching copper and nickel by secondary nickel return according to claim 1, characterized in that: In step S1, the specific process of smelting in a reducing atmosphere is: first heating to 600-700°C, keeping warm for 1-2 hours, then heating to 1000-1100°C, keeping warm for 1-2 hours.

6. The process for enriching copper and nickel by secondary nickel return according to claim 1, characterized in that: In step S2, the solid-liquid ratio of the alloy material to the sulfuric acid solution is 1 g:10-20 mL.

7. The process for enriching copper and nickel by secondary nickel return according to claim 1, characterized in that: In step S2, the mass ratio of the alloy material to sodium chlorate is 1:2-2.

5.

8. The process for enriching copper and nickel by secondary nickel return according to claim 1, characterized in that: In step S2, the temperature of the heating leaching is 70-80° C., and the time of the heating leaching is 6-8 hours.

9. The process for enriching copper and nickel by secondary nickel return according to claim 1, characterized in that: In step S3, the volume ratio of the leachate to the hydrogen peroxide solution is 1:2-4.

Citation Information

Patent Citations

  • Method for enriching copper and nickel from secondary nickel return material of copper smelting slag

    CN113430386A

  • Sorting and recycling treatment method for copper and nickel in copper smelting slag

    CN113481376A

  • Process for separating copper and nickel from secondary nickel return material

    CN119320875A

  • Method for separating and recovering lead, tin and nickel from solder-containing nickel alloy

    JP1999106846A

  • Method of smelting tin

    JP2010280949A